Wakaf Produktif (Perspektif Tafsir Al-Manar) Tafsir Surat Surat Al-Baqarah Ayat 261-263 Dan Surat Ali ‘Imran Ayat 92 - Ramadhan, M.Syafrie; Pratama, M. Guntur Sandi; Aprilianti, Eka (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2024)
Waqf is a social worship contact between humans and Allah SWT, Productive Waqf is found in the Al-Quran verses about nafkah, namely Surah Al-Baqoroh verses 261-263 and Surah Al-'Imran verse 92. The method used is Hermeunetics with the perspective of Al-Manar interpretation. In fact, the Qur'an does not explain the meaning of waqf clearly, but the scholars agree that in the Qur'an what is meant by waqf here is infaq. This is because the basis used by the scholars in explaining the concept of waqf is based on the findings of the Qur'anic verses that explain infaq. Among them are Surah Al-Baqarah verses 261-263 and Al-Imran verse 92.